Effect of community relationship management, customer engagement, and brand trust on food supplement brand loyalty - Wongsuphasawat, Tul; Buatama, Urusa (My University, 2019)
Social media have revolutionized the behavior of people, perceptions, decision processes, and levels of engagement with a brand. There are a number of empirical studies on the impact of the social media on community relationship management, customer engagement, brand trust, and brand loyalty, but not regarding food supplements. Global health and beauty supplement sales have been continuously growing, employing both traditional and digital media channels for promotion. The purpose of this research was to understand the factors in the social media that affect food supplement brand loyalty in Thailand in order to develop a more efficient marketing program. Confirmatory factor analysis was used to analyze structural equation modeling. In total, 508 young Thais living in Bangkok, Thailand participated in this study. The results showed that community relationship management has a direct impact on customer engagement but it bears no direct influence on brand trust and brand loyalty (p <.001). The model explained 69.3 percent of brand loyalty variation. It is clear that by keeping customers engaged, the level of trust and loyalty would increase over time.
Keywords: Brand loyalty; Brand trust; Community relationship management; Customer engagement; Social media